(untitled) - Chisholm, Michael (London, 1973)
This book introduce about geography anf economics, the location problem, scale and variability. Divisobility and mobility of factors of production, demand, trade and substitution, pricing policies...
Keywords: Địa lý kinh tế,Economic geography